Tracking spatial distribution of human-derived wastewater from Davis Station, East Antarctica, using δ15N and δ13C stable isotopes - Patricia Corbett; CK King; Julie Mondon (2015)
Stable isotope ratios, δ15N and δ13C were effectively used to determine the geographical dispersion of human derived sewage from Davis Station, East Antarctica, using Antarctic rock cod (Trematomus bernacchii). Fish within 0-4 km downstream of the outfall exhibited higher δ15N and δ13C values relative to reference sites. Nitrogen in particular showed a stepped decrease in δ15N with increasing distance from the discharge point by 1-2‰. Stable isotopes were better able to detect the extent of wastewater contamination than other techniques including faecal coliform and sterol measures. Uptake and assimilation of δ15N and δ13C up to 4 km from the outfall adds to growing evidence indicating the current level of wastewater treatment at Davis Station is not sufficient to avoid impact to the surrounding environment. Isotopic assimilation in T. bernacchii is a viable biomarker for investigation of initial sewage exposure and longer term monitoring in the future.